The causal effect of including standards-related documentation into patent prior art: Evidence from a recent EPO policy change - Rudi Bekkers; Arianna Martinelli; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
The aim of this paper is to investigate the causal effect of a recent attempt undertaken by the EPO to improve the quality of the patent granting process. To do so we examine a policy change that aimed at including the information revealed during the standardisation-setting process into the official definition of prior art. All the empirical analysis consistently support that the policy was successful. Indeed, we find a negative and strongly significant reduction in the granting rate, suggesting that the process of patent granting has become more careful and selective after the policy implementation.
Keywords: O30; O31; C21; 330; Quality of patent granting; technological standards; policy evaluation